Analisis Kendala Usaha Mikro, Kecil dan Menengah (UMKM) Di Kabupaten Bandung - Saputri, Pelangi Angga; Khomsatun, Siti; Ginanjar, Sunandie Eko (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2024)
MSMEs are businesses owned and run by households, small business entities, groups or individuals. As a developing country, Indonesia places MSMEs at the center of the regional economy to encourage the potential for independence to grow in society, especially in the economic sector. In Indonesia, MSMEs cannot be eliminated because the distribution of people's income is greatly helped by their existence. This research was conducted to determine the restrictive factors (barriers) in the development of MSMEs in Bandung Regency. This study aims to analyze the potential of small and medium-scale creative industries in Bandung Regency to increase income. This research uses qualitative methods with a descriptive-comparative research type. From the studies above, several important factors that influence the development of MSMEs in Bandung Regency include media factors for promotion and marketing, as well as other factors that were not researched. Apart from that, the implementation of the People's Business Credit (KRU) policy and the use of audit designs are also concerned with increasing the income and performance of MSMEs in Bandung Regency. This research has benefits for researchers and readers in identifying obstacles, increasing income, and analyzing the implementation of relevant policies for the development of MSMEs in Bandung Regency.